Kinetic and thermodynamic comparative study of quince bio-waste slow pyrolysis before and after sustainable recovery of pectin compounds - Torres Sciancalepore, Rodrigo Agustin; Fernandez Brizuela, Anabel Alejandra; Asensio, Daniela Anabel; Riveros Gomez, Mathias Adrián; Fabani, Maria Paula; Fouga, Gastón Galo; Rodriguez, Rosa Ana; Mazza, German Delfor (Pergamon-Elsevier Science Ltd, 2022)
Fil: Torres Sciancalepore, Rodrigo Agustin. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación y Desarrollo en Ingeniería de Procesos, Biotecnología y Energías Alternativas. Universidad Nacional del Comahue. Instituto de Investigación y Desarrollo en Ingeniería de Procesos, Biotecnología y Energías Alternativas; Argentina